Investigating World Englishes: Research Methodology and Practical Applications Peter I. De Costa, Dustin Crowther and Jeffrey Maloney (eds) (2019) - Ugwuanyi, Kingsley Oluchi (Sociolinguistic Studies, 2021)
Investigating World Englishes: Research Methodology and Practical Applications Peter I. De Costa, Dustin Crowther and Jeffrey Maloney (eds) (2019) London and New York: Routledge ISBN: 978-1-138-23743-8. Pp. 186